La formazione degli insegnanti come motore dell’innovazione - Venanzi, Mariano (Chimica nella Scuola, 2024)
In this work, we briefly introduce the different levels of training (initial, in-service) of school teachers and academic staff in view of the new law approved in June 2022. The state of art of the organization of the different teacher training programs has been described and briefly commented, focusing on their priorities and critical issues.